STRATEGI PEMENANGAN PASANGAN CALON WALIKOTA DAN WAKIL WALIKOTA INCUMBENT PADA PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA PEKANBARU TAHUN 2017 - M Rico Nurhidayat; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted with the aim of describing how the strategy of winning the incumbent candidate for Mayor and Deputy Mayor in the 2017 Mayor and Deputy Mayor Election. Seeing the problems that exist in Pekanbaru City in one period of Firdaus's leadership - Ayat Cahyadi, there are many problems in various fields , however, the incumbent candidate pair of Pekanabaru City was re-elected to serve as Mayor and Deputy Mayor and will re-lead Pekanbaru City 2018-2022. Problems that existed in Pekanbaru City during Firdaus-Ayat Cahyadi's leadership were packaged into a political issue to attack incumbent couples. The theories used in this study were: strategy, party coalition, and issue management. This study uses a descriptive method with a type of qualitative research. The type of data used in this study is primary data and secondary data obtained through direct interviews with informants who are considered to know and understand the problems that exist in the field, documentation and observation. The inning team took advantage of the moment to approach the community by offering hospitality and delivering solutions offered by the incumbent candidate pair to anticipate the problems that exist in Pekanbaru City, conveying the achievements of the incumbent candidate pairs and conveying their vision and mission to continue the programs that have not been achieved maximally in the process of winning incumbent candidate pairs in the election of Mayor and Deputy Mayor of Pekanbaru in 2017Keyword: Winning Strategy, Issue Management  Keywords: Coordination, Prevention, Flood.